Feeding Ecology of Curlew Sandpiper, Calidris ferruginea, During Spring Stopover in the Sivash Bay (Ukraine) - Khomenko, S.V. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Краснозобики, Calidris ferruginea Pontoppidan, 1763, которые скапливаются в соленой части Сиваша, способны высокоэффективно использовать артемию (Artemia salina) в качестве основного корма. Доказывается, что птицы питаются исключительно днем (до 80% времени наблюдений). Дополнительный энергетический доход составляет в среднем 146,3 ± 38,4 кДж/сут. За счет этого песочники ежедневно увеличивают массу тела в среднем на 4,3 ± 1,1 г. Общий прирост массы за 5–6 дней пребывания на Сиваше составляет до 33—41% усредненной массы тела зимой. Именно наличие на Сиваше такого массового и легкодоступного корма как артемия делает этот водоем привлекательным для десятков тысяч мигрирующих краснозобиков. Curlew Sandpipers, Calidris ferruginea Pontoppidan, 1763, gathering in the galinic part of the Sivash are able to efficiently forage on Brine Shrimps (Artemia salina) using it as a main food. It has been proved, that the birds feed exclusively in day-time (up to 80% of the observation time). Additional energy income makes on average 146.3 ± 38.4 kJ/day. At the expense of this, sandpipers increase body mass at an average rate of 4.3 ± 1.1 g/day. During 5–6 day’s stay at the Sivash their total body mass increases up to 33–41% compared to the average lean (winter) body mass. It is the Brine Shrimps, highly abundant and easily available food, that attracts tens of thousand migratory Curlew Sandpipers to the Sivash.